2008
DOI: 10.1109/tasc.2008.922391
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Critical State Response in Thin Films by AC Susceptibility Measurements

Abstract: Abstract-Low frequency ac magnetic response of the Nb thin film in perpendicular oscillating applied fields is detected by continuously reading SQUID magnetometer. Harmonic analysis of the temperature dependence of the nonlinear ac susceptibility gives excellent agreement with the susceptibility calculated on basis of model of the hysteretic critical state in 2D disk. This complete analytical model relates to Bean's critical state described by the critical depinning current density. We map the experimental and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…Low-T c superconductors were investigated a long time ago [1][2][3] and revealed an absorption maximum at the transition upon variation of temperature and dc magnetic field. The ac response of high-T c superconductors exhibits similar features [4][5][6]. However, the physical reasons for this behavior remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-T c superconductors were investigated a long time ago [1][2][3] and revealed an absorption maximum at the transition upon variation of temperature and dc magnetic field. The ac response of high-T c superconductors exhibits similar features [4][5][6]. However, the physical reasons for this behavior remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The ac magnetic response contains essential information about the properties of superconductors. Peculiarities of the ac response of conventional and high-T c superconductors have been a matter of extensive research [1][2][3][4][5][6]. Low-T c superconductors were investigated a long time ago [1][2][3] and revealed an absorption maximum at the transition upon variation of temperature and dc magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The first was an 8-pixel array consisting of STJs with a size of 50 × 50 µm 2 , which was used to measure the full currentvoltage (I-V ) curves. Because the critical current (I C ) of the superconducting Nb wirings (cross-section ∼ 1.2 × 10 −7 cm 2 ) used in the STJs was less than 0.1 Å, [7] it was necessary to use STJs with a size of 50 ×50 µm 2 to prevent the current flow in the Nb wirings from exceeding the I C values of the Nb wirings when J C was measured. The second was a 100-pixel array of STJs with a size of 100 × 100 µm 2 , which was used to evaluate the x-ray detection performance.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper we reanalyze earlier measurements on Nb film [6] using a method first applied to the YBCO wire and we compare the results.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that this model correctly predicts the response of the YBCO wire and allows estimate in a contactless way the critical current density and its temper-ature dependence [5]. In this paper we reanalyze earlier measurements on Nb film [6] using a method first applied to the YBCO wire and we compare the results.…”
mentioning
confidence: 99%